In vitro apoptotic activity of Lablab purpureus (L.) Sweet low-molecular-weight peptides - SIPAHLI, Shivon; DWARKA, Depika; AMONSOU, Eric; MELLEM, John (Food Science and Technology, 2023)
Cancer prevalence is a rapidly growing concern globally. Traditional treatment protocols, radiotherapy, and chemotherapy are associated with adverse side effects on the human body. Therefore, there is a need for alternative therapies. Peptides from leguminous protein are known for exhibiting positive biological activity that could target cancer cells and minimize side effects. This study assessed the apoptotic ability of peptide fractions 2. The fraction was derived from the pepsin hydrolysate of Lablab purpureus that was fractionated by ultrafiltration and subsequently by reverse-phase high-pressure liquid chromatography. The markers of apoptosis (caspase-9 and -3, p53, and annexin V-PI) were then observed for efficacy. Caspase-9 and -3 showed activity to a greater degree in cancerous cell line A549 (2.3-fold and 1.1-fold) and MCF-7 (2.7-fold and 1.8-fold), respectively, compared to camptothecin (positive control). Expression of p53 on treated cancerous cell lines (A549 and MCF-7) demonstrated greater ability over the non-cancerous cell line (HEK293) with A549 showing the highest activity at 29.923 µg/mL. Finally, annexin V-PI staining sorted cells into phases of apoptosis. Treated A549 and MCF-7 cells detected 85.4% and 89.6% of cells undergoing apoptosis. Overall, Fraction 2 triggered apoptosis in cancer cell lines while minimally harming non-cancerous cells.